Extraction, Colour Stability, and Antioxidant Activity of Anthocyanins from Binahong Fruits (Anredera cordifolia) for Natural Lipstick Colorants - Wathon, Muhammad Hizbul; Vannesha Vivian Putri; Sri Mulyani; Sri Retno Dwi Ariani; Elfi Susanti VH; Suryadi Budi Utomo (The Journal of Pure and Applied Chemistry Research, 2026)
Rising demand for natural colorants, coupled with health concerns over synthetic dyes such as Red K3 and Red K10, motivates the development of plant-based alternatives for cosmetics applications. Here, we formulated lipstick incorporating anthocyanins extracted from Binahong (Anredera cordifolia) fruits using acidified water (0.01% HCl, v/v) and purified via Amberlite XAD-7 HP resin. Refined Binahong fruit extract (RBFE) was analyzed by UV-Vis spectrophotometry and LC-MS, which classified its anthocyanins as C-type based on absorbance patterns at pH 1 and 4.5. This indicating an acyl groups on the B-ring. Four anthocyanins were identified: pelargonidin-3-O-glucoside (m/z 433), pelargonidin-3-O-(6”-malonyl) glucoside (m/z 519), petunidin-3-O-(6”-malonyl) glucoside (m/z 565), and cyanidin-3-O-rutinoside (m/z 595). Anthocyanins exhibited a bathochromic sshift with increasing pH and greater stability under acidic, refrigerated storage than at room temperature. Lipsticks formulated with 0-25% anthocyanins met SNI standards for pH and melting point. Antioxidant activity (IC50) improved with anthocyanins concentration, ranging from 24.52 ppm (0%) to 18.20 ppm (25%), compared to 12.91 ppm for Trolox and 15.02 ppm for RBFE. Higher anthocyanin concentration also produced more intense red coloration, demonstrating Binahong fruit's potential as a functional, health-conscious colorant for cosmetics formulations.